Bertolt Brecht? „Il n’y a pas de hors-texte” - Karasińska, Marta (Wydawnictwo Naukowe UAM, 2009)
With his theory of the epic theatre and its most important category V-Effekt, Bertolt Brecht can be included within precursors of the current of modern reflection on discourse, crisis of representation and transitivity of that which is literary with that which is theatrical, the stage character of the text and textuality of the stage. Disproving of the role of mimesis, the importance of quotation and repetition as rudimentary acting strategy, replacement of great narrations with a fragment, joining a work and a commentary, intertextual games, metatextuality and metatheatricality as a foundation of stage aesthetics encourage us to locate Brecht’s theatrical output in the context of reflection of Deridda, Foucault and Barthes.
Bertolt Brecht? Il n’y a pas de hors-texte